Perceptions and practices of medical ethics and laws among health professionals in Abu Dhabi, United Arab Emirates - Emad Abdel Rahim Dahiyat; Ammar Abdulrahman Jairoun; Faris El-Dahiyat (Humanities & Social Sciences Communications)
Abstract The flourishing of health care relies on not only the quality of medical infrastructure but also legal and ethical frameworks, as well as the extent to which these are followed by physicians and nurses. This study aimed to evaluate the perceptions and practices of medical ethics and laws among healthcare professionals in Abu Dhabi, United Arab Emirates. A cross‐sectional study was conducted between May 10, 2023, and August 22, 2023, at five medical centres in Abu Dhabi. During the study period, self-administered surveys consisting of three sections were distributed to a random sample of physicians and nurses. The first section of the questionnaire included questions addressing the respondents’ demographic data, and the second and third sections assessed the respondents’ perceptions of and practices regarding adherence to the regulations governing healthcare providers. A total of 438 healthcare professionals participated in the study. Their mean age was 55.6 ± 11.3 years. Overall, the levels of perception and practice concerning medical ethics and healthcare laws were good. Specialist and junior physicians demonstrated higher levels of perception compared to junior nurses, with scores of 88.54% versus 65.25% and 78.85% versus 65.25%, respectively. The study reveals the need to revise the curricula of medical institutions to enhance health practitioners’ legal knowledge, attitudes and practices.